1980
DOI: 10.1007/bf00234879
|View full text |Cite
|
Sign up to set email alerts
|

Changes in nucleolar dry mass of neurones of the paraventricular and supraoptic nuclei in the rat during pregnancy and lactation

Abstract: Interference microscopy was used to measure the dry mass of nucleoli in unfixed nuclei isolated from neurones of the paraventricular (PV) and supraoptic (SO) nuclei of female rats. Changes in nucleolar dry mass during pregnancy and lactation have been interpreted as reflecting changes in rates of synthesis of ribosomes and protein in these neurones. Measurements were made on a total of 6580 nucleoli from 135 rats. At the end of pregnancy nucleolar dry mass of both PV and SO neurones was increased compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1980
1980
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Since our previous studies (Stern & Armstrong, 1996; Teruyama & Armstrong, 2002 a ) had suggested a common feature of AHP and DAP plasticity might be their Ca 2+ dependence, we tested whether AHP plasticity was related to changes in the whole‐cell Ca 2+ current or in [Ca 2+ ] i . Although whole‐cell Ca 2+ current did increase coincident with the somatic hypertrophy of OT neurons during lactation observed previously (Russell, 1980; Theodosis & Poulain, 1993; Brussaard et al 1999), current density was not increased. Neither did the peak Ca 2+ transient (Δ F / F ).…”
Section: Discussionsupporting
confidence: 55%
“…Since our previous studies (Stern & Armstrong, 1996; Teruyama & Armstrong, 2002 a ) had suggested a common feature of AHP and DAP plasticity might be their Ca 2+ dependence, we tested whether AHP plasticity was related to changes in the whole‐cell Ca 2+ current or in [Ca 2+ ] i . Although whole‐cell Ca 2+ current did increase coincident with the somatic hypertrophy of OT neurons during lactation observed previously (Russell, 1980; Theodosis & Poulain, 1993; Brussaard et al 1999), current density was not increased. Neither did the peak Ca 2+ transient (Δ F / F ).…”
Section: Discussionsupporting
confidence: 55%
“…It has been suggested that the cellular hypertrophy probably reflects increased synthesis of neurohormones [Sokol and Vaitin. 1965], An increment of nuclear area has also been reported in the hypothalamic neurosecretory neurons during preg nancy and lactation, which produce an increased demand of oxytocin [Russell, 1980] and in rats drinking hypertonicsolutions to create a chronic increase in plasma osmolality, which results in an increase in vasopressin production [Enestrom, 1967: Paterson andLeblond. 1977].…”
Section: Morphometric Analysismentioning
confidence: 99%
“…Taken together, these data show that the 5‐HT inhibitory influence on VIP gene expression and probably on peptide synthesis during prenatal ontogenesis is reversible. Lack of stimulating influence of 5‐HT deficiency on VIP and VP synthesis is indirectly confirmed by the absence of neuron hypertrophy (see Results) (Russel, 1980; Van Tol et al, 1987; McCabe et al, 1990).…”
Section: Discussionmentioning
confidence: 77%